Ischaemic heart disease unmasked by adrenaline injection during dental surgery. Issue 2 (22nd September 2014) - Brown, Hannah; Cook, Tim
Summary: A 56‐yr‐old female presented for multiple dental extractions under general anaesthesia as a day case. Lidocaine with adrenaline administered by the surgeon intraoperatively is suspected to have triggered cardiac ischaemia requiring inpatient coronary artery bypass grafting (CABG). Lidocaine with adrenaline is commonly used in dental surgery and considered safe, even in patients with coronary artery disease. This unusual case is a reminder that systemic absorption of adrenaline can occur and trigger cardiac ischaemia in at risk patients. A high index of suspicion should be maintained if cardiovascular instability occurs and appropriate investigation and follow up instigated.